Credit as a key driver of sustainability and economic recovery of Ukraine - Doroshenko , N.; Chypiha, K. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2023)
The study examines the current topic of bank lending in modern Ukrainian conditions. By analyzing the dynamics of credit activity and the financial condition of banks in Ukraine, the work reveals the main problems affecting this sector, such as a large share of non-performing loans, a decrease in the share of long-term loans, and a high lending rate. The conclusions of the work provide recommendations for improving the situation on the lending market in Ukraine. The modern economy of Ukraine is experiencing complex challenges related to the war in Ukraine, which was preceded by the COVID-19 pandemic and the global economic crisis. In this context, the article examines the role of credit as a key driver of economic stability and post-victory recovery. The study is based on the analysis of available data and literature sources, and also uses empirical methods to determine the impact of lending on economic recovery. The article highlights key aspects of lending, such as the role of banks, loan volumes, interest rates and overdue loans. The results of the study emphasize the importance of the development of the financial sector and the promotion of credit availability for enterprises and the population in the context of the economic recovery of Ukraine. The authors provide practical recommendations for the government and regulators to improve the credit environment and stimulate investment activity. This article is aimed at opening discussions and promoting further research into the role of lending in stimulating the economic recovery of Ukraine in the face of today's extremely complex challenges and may be useful for economists, theoreticians and practitioners. The scientific study analyzes how lending can affect the financial stability of Ukraine, in particular, how it can reduce financial risks and contribute to the stability of the economy. The impact of credit availability for various areas and sectors of the economy is considered. The article offers an important contribution to understanding and improving the effectiveness of lending as a tool for the economic recovery of Ukraine, emphasizing the need for a coordinated approach to this issue, taking into account the unique challenges and opportunities that exist at this stage of the country's development.